THE IMPACT OF 6-MONTH DELAY IN DIAGNOSIS ON CLINICAL AND FUNCTIONAL STATUS IN THE PSA PATIENTS UNDER BDMARD TREATMENT: RESULTS FROM TREASURE DATABASE - Ayan, G.; Kilic, L.; Bilge, N. S. Yasar; Atagunduz, P.; Dalkilic, E.; Pehlivan, Y.; Kalyoncu, U. (Bmj Publishing Group, 2023)
[Abstract Not Available]
European Congress of Rheumatology (EULAR) -- MAY 31-JUN 03, 2023 -- Milan, ITALY
Keywords: Registries; Psoriatic arthritis; Real-world evidence